Neutral nuclear variation in Baboons (genus Papio) provides insights into their evolutionary and demographic histories. Issue 4 (19th September 2014) - Boissinot, Stéphane; Alvarez, Lauren; Giraldo‐Ramirez, Juliana; Tollis, Marc
ABSTRACT Baboons (genus Papio) are distributed over most of sub‐Saharan Africa and in the southern portion of the Arabian Peninsula. Six distinct morphotypes, with clearly defined geographic distributions, are recognized (the olive, chacma, yellow, Guinea, Kinda, and hamadryas baboons). The evolutionary relationships among baboon forms have long been a controversial issue. Phylogenetic analyses based on mitochondrial DNA sequences revealed that the modern baboon morphotypes are mitochondrially paraphyletic or polyphyletic. The discordance between mitochondrial lineages and morphology is indicative of extensive introgressive hybridization between ancestral baboon populations. To gain insights into the evolutionary relationships among morphotypes and their demographic history, we performed an analysis of nuclear variation in baboons. We sequenced 13 noncoding, putatively neutral, nuclear regions, and scored the presence/absence of 18 polymorphic transposable elements in a sample of 45 baboons belonging to five of the six recognized baboon forms. We found that the chacma baboon is the sister‐taxon to all other baboons and the yellow baboon is the sister‐taxon to an unresolved northern clade containing the olive, Guinea, and hamadryas baboons. We estimated that the diversification of baboons occurred entirely in the Pleistocene, the earliest split dating ∼1.5 million years ago, and that baboons have experienced relatively large and constant effective population sizes for most of their evolutionary history (∼30, 000 to 95, 000 individuals). Am J Phys Anthropol 155:621–634, 2014. © 2014 Wiley Periodicals, Inc.